ANALISIS PENGARUH PENERAPAN IFRS,OPINI AUDIT,UKURAN KAP, DAN PROFITABILITAS TERHADAP KETERLAMBATAN PENYAMPAIAN LAPORAN KEUANGAN : Studi Empiris Pada Perusahaan Manufaktur Sektor Perdagangan, Jasa & Investasi yang terdaftar di Bursa Efek Indonesia - Fanny Lubis; Restu Agusti; Yesi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
There are several factors that affect the company’s delay in submitting the financial statement are often reffered to as Audit Delay, among others IFRS (International Financial Reporting Standards), Audit Opinion, Size Public Accounting Firm and Profitability. One factor that is quite prominent is the application of IFRS that have not been uniform across all companies in Indonesia. It could also lead to Audit Delay. Public Accounting Size theoretically means companies bigger scale required to submit financial reports on time. As for Audit Opinion and Profitability is also decent enough to be considered as one of the influential factors on Audit Delay. The results of this study indicate that the application of IFRS, Audit Opinion and KAP Size have a significant impact on the delay for submission of financial statement. And KAP Size does not have a significant impact.Keywords: IFRS,Audit Opinion,KAP size and Profitability